Characteristics of Effective English Teacher for Millenials - Andi Wirantaka; Putri Anggia Wahyudianawati (Journal of Foreign Language Teaching and Learning, 2021)
The millennial era is an era of digital technology in which people are close to technology and have instant access to information. This study investigated students' perception of the characteristics of an effective English language teacher in the millennial era. This study used a qualitative approach and used a descriptive qualitative design and took place at a private university in Yogyakarta. The participants were four students of the English Language Education Department (ELED) batch 2016. In collecting the data, the researcher interviewed the participant. The findings showed that in socio-affective skills, an effective English language teacher in the millennial era should enhance students' motivation to learn, create a good classroom atmosphere, have good relationships with the students and other teachers, and understand students' character. In pedagogical knowledge, an effective English language teacher should give feedback, have a valuable ability to explain the lesson, ensure students' understanding of the lesson. They also should have a lesson plan, utilize and apply technology, allow students to write a reflection, and control class activities. In knowledge subject matter, an effective English language teacher should be knowledgeable and master English well. Lastly, an effective English language teacher should have personality traits such as intelligent, caring, friendly, disciplined, creative, kind, patient, humorous, responsible, open-minded, and professional. The findings implied that to teach students in the millennial era effectively, teachers should possess and maintain the characteristics of an effective English language teacher.